In silico prediction of functional loss of cst3 gene in hereditary cerebral amyloid angiopathy - Choudhary, Piyush; Singh, Juhee; Karthick, V.; Shanthi, V.; Rajasekaran, R.; Ramanathan, Karuppasamy (Bangladesh Journal of Pharmacology, 2013)
The computational identification of missense mutation in CST3 (CYSTATIN 3 or CYSTATIN C) gene has been done in the present study. The missense mutations in the CST3 gene will leads to hereditary cerebral amyloid angiopathy The initiation of the analysis was done with SIFT followed by POLYPHEN-2 and I-Mutant 2.0 using 24 variants of CST3 gene of Homo sapiens which were derived from dbSNP. The analysis showed that 5 variants (Y60C, C123Y, L19P, Y88C, L94Q) were found to be less stable and damaging by SIFT, POLYPHEN-2 and I-MUTANT2.0. Furthermore the outputs of SNP & GO are collaborated with PHD-SNP (Predictor of Human Deleterious-Single Nucleotide Polymorphism) and PANTHER to predict 5 variants (Y60C, Y88C, C123Y, L19P, and L94Q) having clinical impact in causing the disease. These findings will be certainly helpful for the present medical practitioners for the treatment of cerebral amyloid angiopathy.